MORAL FACTS AS CONFIGURING CAUSES. - Cuneo, Terence (Pacific Philosophical Quarterly, 2006)
The overarching aim of this essay is to argue that moral realists should be “causalists” or claim that moral facts of certain kinds are causally efficacious. To this end, I engage in two tasks. The first is to develop an account of the sense in which moral facts of certain kinds are causally efficacious. After having sketched the concept of what I call a “configuring” cause, I contend that the exercise of the moral virtues is plausibly viewed as a configuring cause. The second is to show that the causalist position I develop can withstand objections inspired by the work of Robert Audi and Jaegwon Kim.